2007
DOI: 10.1016/j.cell.2007.05.059
|View full text |Cite
|
Sign up to set email alerts
|

M. tuberculosis and M. leprae Translocate from the Phagolysosome to the Cytosol in Myeloid Cells

Abstract: M. tuberculosis and M. leprae are considered to be prototypical intracellular pathogens that have evolved strategies to enable growth in the intracellular phagosomes. In contrast, we show that lysosomes rapidly fuse with the virulent M. tuberculosis- and M. leprae-containing phagosomes of human monocyte-derived dendritic cells and macrophages. After 2 days, M. tuberculosis progressively translocates from phagolysosomes into the cytosol in nonapoptotic cells. Cytosolic entry is also observed for M. leprae but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
825
3
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 868 publications
(875 citation statements)
references
References 52 publications
34
825
3
13
Order By: Relevance
“…Bacterial levels at 24‐hr postinfection (hpi) were analysed with FACS and compared with uptake of these bacteria by RAW macrophages. RAW macrophages phagocytosed both strains with similar efficiency, both at 2 and 24 hpi (Figure 7a), confirming previous reports that the level of phagocytosis of M. marinum WT and our esx‐1 mutant are similar (Houben et al, 2012; Simeone et al, 2012; van der Wel et al, 2007). …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Bacterial levels at 24‐hr postinfection (hpi) were analysed with FACS and compared with uptake of these bacteria by RAW macrophages. RAW macrophages phagocytosed both strains with similar efficiency, both at 2 and 24 hpi (Figure 7a), confirming previous reports that the level of phagocytosis of M. marinum WT and our esx‐1 mutant are similar (Houben et al, 2012; Simeone et al, 2012; van der Wel et al, 2007). …”
Section: Resultssupporting
confidence: 89%
“…ESX‐1 secretion mutants are severely attenuated (Davis & Ramakrishnan, 2009; Stoop et al, 2011; Volkman et al, 2004), but most importantly for our purposes, these mutants are unable to complete the macrophage infection cycle and are therefore predominantly located inside phagocytic cells (Houben et al, 2012; Simeone et al, 2012; van der Wel et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant BCG::RD1-strain expressing the ESAT-6 secretion system showed similar TB10.4 epitope recognition patterns as virulent M.tb, both recognizing the MHC-I restricted epitopes in P1 and P2 and the MHC-II restricted epitope in P8 (data not shown), corresponding to earlier described epitopes [24,26,27]. As it has been suggested that the RD1 region enables M.tb to escape the phagosome [28], it could be speculated that altered intracellular trafficking of BCG might lead to a different epitope pattern and/ or to new protective epitopes.The comparison of the CD4 1 T-cell responses induced in our study revealed that BCG and M.tb both induced T cells specific for the known epitope residing in TB10.4-P8 [27], whereas P3 and P7 were the main epitopes recognized following TB10.4 vaccination, in agreement with an earlier study ( Fig. 1 and 2 [15]).…”
supporting
confidence: 65%
“…In vitro studies using electron microscopy (EM) and a fluorescence resonance energy transfer‐based method showed that Mtb also localizes in the cytosol in THP‐1 macrophages, primary human macrophages and primary human DCs (van der Wel et al ., 2007; Houben et al ., 2012; Simeone et al ., 2012). The ESX‐1 type VII secretion system (T7SS) that is lacking from most of the non‐pathogenic mycobacterial strains (Abdallah et al ., 2007) is required for Mtb localization in the cytosol.…”
Section: Cell Autonomous Defence Mechanisms In Tbmentioning
confidence: 99%